1996
DOI: 10.1104/pp.112.2.463
|View full text |Cite
|
Sign up to set email alerts
|

Transduction of an Ethylene Signal Is Required for Cell Death and Lysis in the Root Cortex of Maize during Aerenchyma Formation Induced by Hypoxia

Abstract: Ethylene has been implicated in signaling cell death in the lysigenous formation of gas spaces (aerenchyma) in the cortex of adventitious roots of maize (Zea mays) subjected to hypoxia. Various antagonists that are known to modify particular steps in signal transduction in other plant systems were applied at low concentrations to normoxic and hypoxic roots of maize, and the effect on cell death (aerenchyma formation) and the increase in cellulase activity that precedes the appearance of cell degeneration were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
161
0
25

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(195 citation statements)
references
References 54 publications
7
161
0
25
Order By: Relevance
“…Em uma série de experimentos com raízes de plantas de milho sob hipóxia, no último artigo da série (He et al 1996) foi observado que quando ocorre hipóxia, há um aumento na síntese de etileno pelo aumento da atividade de ACC sintase, o que resulta em um aumento na atividade de celulase que contribui para a degradação da parede celular e a formação de aerênquima do tipo lisígeno. Os autores ainda bloquearam a síntese de etileno usando aminoetoxilvinilglicina (AVG), o que suprimiu o aumento de celulase e a formação do aerênquima.…”
Section: Sinalização Metabólica E Hormonal Durante O Alagamentounclassified
See 1 more Smart Citation
“…Em uma série de experimentos com raízes de plantas de milho sob hipóxia, no último artigo da série (He et al 1996) foi observado que quando ocorre hipóxia, há um aumento na síntese de etileno pelo aumento da atividade de ACC sintase, o que resulta em um aumento na atividade de celulase que contribui para a degradação da parede celular e a formação de aerênquima do tipo lisígeno. Os autores ainda bloquearam a síntese de etileno usando aminoetoxilvinilglicina (AVG), o que suprimiu o aumento de celulase e a formação do aerênquima.…”
Section: Sinalização Metabólica E Hormonal Durante O Alagamentounclassified
“…He e colaboradores (He et al 1996) também mostraram que a manipulação da concentração e fluxo de cálcio citoplasmático pode alterar a capacidade de resposta de raízes de milho à hipóxia com a formação de aerênquima. Alterar os níveis de cálcio é importante não somente para os mecanismos de sinalização intracelulares mas, também, para que as pectinas, que formam complexos com o cálcio na parede celular, se tornem acessíveis ao ataque de enzimas.…”
Section: Sinalização Metabólica E Hormonal Durante O Alagamentounclassified
“…RCA has been primarily studied as a response to hypoxic conditions and improves oxygen transport to the root tip and rhizosphere (He et al 1996;Evans 2004;Thomas et al 2005) which has been shown to be particularly important in submergence tolerance in rice (Ito et al 1999). Presumably, RCS which culminates in a non-continuous epidermis, has no utility in hypoxic conditions.…”
Section: Rcs and Nutrient Remobilizationmentioning
confidence: 99%
“…A first attempt to elucidate these was the application of inhibitors and elicitors of programmed cell death (PCD) that were previously used successfully in animal systems or with other PCD processes in plants (He et al, 1996b). K252a, a substance that inhibits protein kinases and protein kinase C in particular, inhibited both cellulase activity and aerenchyma formation under low oxygen concentrations, suggesting a role for protein kinase C in the induction of aerenchyma.…”
Section: Down-stream Parts Of the Signal Transduction Pathwaymentioning
confidence: 99%
“…K252a, a substance that inhibits protein kinases and protein kinase C in particular, inhibited both cellulase activity and aerenchyma formation under low oxygen concentrations, suggesting a role for protein kinase C in the induction of aerenchyma. On the other hand, specific inhibition of protein phosphatases 1 and 2A by applying okadaic acid (Cohen et al, 1990) is supposed to enhance protein phosphorylation and proved to promote cellulase activity and aerenchyma formation (He et al, 1996b). Similarly, GTPγ S, which is capable of locking G-proteins in the active state, increased the volume of aerenchyma under normoxic conditions, whereas its analogue GDPβS, which inactivates the proteins, did not have effect on the aerenchyma content, neither under normoxic nor under low-oxygen conditions.…”
Section: Down-stream Parts Of the Signal Transduction Pathwaymentioning
confidence: 99%